The Effectiveness of Schema Therapy on Marital Relationships and Cognitive Emotion Regulation in Couples on the Verge of Divorce - Abedi , Seyedeh Fatemeh; Ashoori , Sahar; Jalili , Mehdi; Aminzadeh , Arezoo; Shirani, Bahar (KMAN Counseling & Psychology Nexus, 2024)
This study aimed to determine the effectiveness of schema therapy on marital relationships and cognitive emotion regulation in couples on the verge of divorce. The research method was quasi-experimental with a pretest-posttest design and a control group. The statistical population of the study included couples on the verge of divorce who referred to counseling centers in Tehran during the first three months of 2024. The sampling method was convenience sampling. A total of 32 individuals on the verge of divorce were selected and randomly assigned to an experimental group (n = 16) and a control group (n = 16). To collect data, the Marital Relationship Questionnaire and the Cognitive Emotion Regulation Questionnaire were used. Schema therapy sessions were then conducted for the experimental group over 8 sessions (two 90-minute sessions per week) based on a protocol developed by the researcher. The findings showed that the mean scores of marital relationships and cognitive emotion regulation in couples on the verge of divorce were significantly different in the posttest compared to the pretest. As a result, schema therapy has an effect on improving marital relationships and cognitive emotion regulation in couples on the verge of divorce.